CHARACTERISTICS OF MADURA JAMU HERBALIST AND TRADITIONAL VALUE PRESERVATION - Ratnawati, Sri (E-Journal of Cultural Studies, 2020)
Compounding herbal medicine that lives in modern times does not automatically release the traditional cultural values ??that have become a hereditary convention, which includes the value of folklore as a spirit of life. They continue to make new innovations to adjust to their times. Innovation does not mean eliminating traditional values, but through traditional change begins. This is done not by setting aside traditional systems that have taken root for decades, but instead by using cultural thinking and traditional values ??tools to direct the vision, mission of Madura herbal medicine from the past to the future. The herbalist of Madura herbal medicine as an agent who sees the importance of putting Madurese cultural values ??on every practice of making Madura herbal medicine. Local cultural values, such as genealogy, oral transmissions and folklore values ??have long given a color to Madura herbal medicine. This means, that the practice of making Madura herbal medicine, is one of the potential local wisdom traditions for the preservation of regional cultural identity in Indonesia.  Keywords: herbal medicine, herbalist, local wisdom, transmission of values, cultural preservation